NEW LATE VENDIAN PALAEOGEOGRAPHY OF BALTICA AND THE TESZ - Nawrocki J.; Boguckij A.; Katinas V. (My University, 2004)
New palaeomagnetic poles obtained from the Vendian tuffs and basalts of western Ukraine indicate the necessity of a substantial revision of the Late Vendian-Early Cambrian palaeogeography of the Baltic plate. The palaeopole calculated for the most stable component iso- lated from the Vendian tuffs and basalts is far away from the Vendian-Cambrian apparent polar wander path (APWP), constructed on the basis of Scandinavian poles but is very close to the pole recently isolated from the Vendian sediments of the White Sea Region. Depend- ing on the polarity of the newly-determined Late Vendian pole, two palaeogeographic models of the Baltic plate in the Late Vendian-Early Cambrian are possible. In our preferred model the Baltic plate moved at that time from the moderate southern latitudes to the equator rotating anticlockwise of ca. 120. This reconstruction explains the geological structures of the marginal zones of Baltica better than the previously proposed stationary model of the Late Vendian-Cambrian Baltica. According to the new late Vendian palaeogeographic scenario, the European, passive margin of Baltica was separated from an active, Avalonian margin of Gondwana. The Late Neoproterozoic tectonic structures of the Brunovistulian Terrane and the Ma³opolska Block were developed near the present day southwestern corner of Baltica that was tectonically active at that time. Alternative reconstruction shows the Baltic plate moving from the moderate northern latitudes in the Vendian, crossing palaeoequator in the latest Vendian, and reaching moderate southern palaeolatitudes in the Late Cambrian. This model, however, would have required exceptionally high plate velocity (ca. 33 cm/year).
Keywords: Baltica; Malopolska; Brunovistulian; Vendian; palaeogeography; palaeomagnetism; Precambrian::Proterozoic::Neoproterozoic::Vendian; Докембрий::Протерозой::Неопротерозойская::Вендский